2013
DOI: 10.1111/jvim.12240
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity and Aldosterone Concentrations in Hypertensive Cats with and without Azotemia and in Response to Treatment with Amlodipine Besylate

Abstract: BackgroundRole of renin‐angiotensin aldosterone system (RAAS) in feline systemic hypertension is poorly understood.ObjectivesExamine plasma renin activity (PRA) and plasma aldosterone concentrations (PAC) in normotensive and hypertensive cats with variable renal function and in response to antihypertensive therapy.AnimalsOne hundred and ninety‐six cats >9 years from first opinion practice.Methods PRA, PAC, and aldosterone‐to‐renin ratio (ARR) were evaluated in cats recruited prospectively and grouped according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 58 publications
(95 reference statements)
6
72
0
1
Order By: Relevance
“…The difference in plasma tMg between normotensive cats and cats with a (previous) diagnosis of systemic hypertension, however, was small, and therefore not directly clinically relevant. Increased plasma aldosterone is commonly observed in azotemic cats with systemic hypertension and not influenced by treatment with amlodipine besylate . It could be a possible link between hypomagnesemia and hypertension, because aldosterone stimulates urinary magnesium excretion whilst magnesium inhibits aldosterone release .…”
Section: Discussionmentioning
confidence: 98%
“…The difference in plasma tMg between normotensive cats and cats with a (previous) diagnosis of systemic hypertension, however, was small, and therefore not directly clinically relevant. Increased plasma aldosterone is commonly observed in azotemic cats with systemic hypertension and not influenced by treatment with amlodipine besylate . It could be a possible link between hypomagnesemia and hypertension, because aldosterone stimulates urinary magnesium excretion whilst magnesium inhibits aldosterone release .…”
Section: Discussionmentioning
confidence: 98%
“…[149][150][151] A study investigating PRA and aldosterone concentration in normotensive azotemic CKD and non-azotemic age matched controls found no significant difference between these variables. 150 Experimental feline studies have demonstrated that administration of ACEi alters renal haemodynamics and reduces proteinuria with the latter observation also been observed in cats with naturally occurring CKD. 143,[152][153][154] However, to date, the survival advantage that we might anticipate from administration of an ACEi has not been demonstrated.…”
Section: Activation Of the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Hypertensive cats have lower plasma potassium concentrations than their normotensive counterparts . However, investigations into the activation of the renin–angiotensin–aldosterone system (RAAS) have reported heterogeneous results . As amlodipine is thought to produce its antihypertensive effects by reducing peripheral resistance, investigations into the factors influencing response to amlodipine could help elucidate the pathophysiologic mechanisms driving hypertension in cats with and without CKD.…”
mentioning
confidence: 99%